Modelling and Control Design for Energy Management of Grid Connected Hybrid PV-wind System - Hassan Abouobaida; Said El Bied (International Journal of Applied Power Engineering (IJAPE), 2018)
This paper deals with the control of hybrid PV-WIND power conversion structure. This paper develops a very important contribution which is the use of a single DC to DC converter, linearization of control of the three- level boost converter (TLBC) considering the imperfections of the passive components. The (TLBC) control provides balancing of capacitor voltages and maximum power operation of PV generator. For reasons of simplicity, a linearization based on the dynamic compensation of the disturbance is proposed. A sensorless maximum power point tracking (MPPT) algorithm is used to maximize a power extracted of the wind generator. The proportional relation between the rotational speed and the output voltage of the rectifier allows to use a voltage sensor to estimate the DC bus voltage reference instead of a mechanical speed sensor. The control of the three-phase inverter allows a transfer of the active power, the power factor close to the unit and thus a limitation of the reactive power injected into the grid. The external control loop performs the regulation of the common DC bus voltage while the internal control loop regulates the dq components of the currents injected into the grid. The simulation results showed the validity of the control approach. The proposed power conversion structure based on a single static converter has shown very good performance in terms of efficiency, the quality of the energy produced, complementarity between the two renewable sources and reliability. The paper ends with conclusions.